Caracterização e utilização de carvões ativados na redução da disponibilidade de chumbo em Latossolo Vermelho Eutroférrico - Silva, Mateus José Falleiros da (2012)
Lead (Pb) soil contamination poses risks to human health. To reduce this, we proposed to incorporate activated carbon to the soil. Initially, we evaluated the correlation between the total lead content (Pbt) and available (Pbd) in 302 soil samples from Paraná State. Then, an Oxisol (Eutroferric Red Latosol - LVef) and two activated charcoals, vegetable (CV) and animal bones (CO) source, were characterized and the lead maximum adsorption capacities (PbMAC) determined. Next, we evaluated the Pb retention and extractability in the soil treated with increasing doses of CV or CO, determining the concentrations of Pb remaining in solution (Pbrem) and retained (Pbret), and Pb extracted by successively extraction with H2O, KCl 1 mol L-1 and Mehlich-1 background solution. Finally, we evaluated the effects of time of treatment with CO and CV on the concentrations of Pb extracted with Mehlich-1 solution, in the contaminated LVef soil, after 3 to 120 days of treatment. The correlation between the levels of Pbt and Pbd in tested soils was weak (r = 0.139), and there was no correlation between the levels of Pbt or Pbd and sand, silt, clay or organic matter contents, in 17 selected soils. Therefore, the content of Pbd soil can be used as auxiliary standart to evaluate the degree of contamination of the soil. The PbMAC of the LVef, CO and CV were, respectively, 3984, 43,478 and 41,667 mg kg-1. The CO showed higher Pbrem than the CV to reduce Pb availability. In successive extraction, there was no significant effect of the CV or CO dose on accumulated extracted Pb content. The CV increased the Pb soluble fraction and decreased the strongly retained one, with no effect on the exchangeable fraction. The CO decreased the soluble and exchangeable Pb fraction, and increased the fraction retained strongly. At a dose of 5% CV or CO tended to increase the content of Pb extracted from the contaminated soil as a function of time, and only treatments with CV reduced Pb content extraction from the soil. It was concluded that the dose of activated carbon to be used in the remediation of Pb may vary depending on the soil characteristics and coal, and the availability of Pb was affected by the treatment time.